International Conference “South Caucasus: Current Challenges to Stability and Security” - Gohar Iskandaryan (Banber Arevelagitut'yan Instituti)
On November 28, 2023, the Institute of Oriental Studies of the National Academy of Sciences of the Republic of Armenia (hereinafter NAS RA) organized an international conference entitled " South Caucasus: Current Challenges to Stability and Security" that took place in the meeting hall of the NAS RA.